Respon dan Pemahaman Tukang Becak terhadap Pelatihan Bahasa Inggris yang Dilaksanakan Pemkab Banyuwangi dalam Menunjang Keberhasilan Wisata - Siti Fatimah; Hari Sukarno; Mohamad Dimyati (e-Journal Ekonomi Bisnis dan Akuntansi, 2017)
Research purposes is to understand the response and understanding of artisan rickshaw about training English carried out thedistrict government Banyuwangi in supporting the success of tourist. Types of research used in this study is the qualitativeresearch. Analyctal methods data in this study includes four seps that data collection, data reduction, data presentation, andconclusion.The conclusion of this research is 1) response artisan rickshaw to the training English language is the artisanrickshaw benefit many of training English especially the following the training to increase income and benfits not only to nowbut also for the future.there is also told his son who take the training and benefits will be felt by his son is, in this case artisanrickshaw that told his son who take training assume that will reduce income when taking part training this is because only seethe short term.2) understanding of artisan rickshaw to the training English language is the artisan rickshaw to introduce thetourist attractions that is in Banyuwangi to the foreign tourists, understand the tourists foreign what kind, interact andcommunicate with foreign tourists, familiar with foreign cultures such as what, attract foreign tourists visiting in the cityBanyuwangi, artisan rickshaw been able to understand the meaning of greeting the tourists, and become builders rickshawtourism awareness. Income derived from the tourist is very different from the local people. So that the ability of artisanrickshaw in communicate using the English language will affect the comfort of foreign tourists visiting to the city Banyuwangi.